2019
DOI: 10.1007/s13300-019-0647-x
|View full text |Cite
|
Sign up to set email alerts
|

Using Clinical Indices to Distinguish MODY2 (GCK Mutation) and MODY3 (HNF1A Mutation) from Type 1 Diabetes in a Young Chinese Population

Abstract: Introduction Accurate diagnosis of maturity-onset diabetes of the young (MODY) is required in order to select appropriate treatment options and to assess prognosis. The aim of this study was to explore potential clinical indicators that could be used to differentiate MODY2, MODY3, and type 1 diabetes (T1D) in young subjects. Methods Twelve patients with MODY3 and 29 patients with MODY2 were characterized and compared to 26 patients with T1D. These three groups were matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Even though patients with MODY were found to differ from T1DM patients in several clinical predictors, such as C-peptide concentration [ 114 ], hsCRP [ 115 , 116 , 117 ], lipid levels, polyuria or age at diagnosis, still around 38% of the MODY patients are misdiagnosed with T1DM or T2DM [ 27 , 87 , 118 , 119 , 120 ]. In 2013 Steele et al reported that age-related glycated haemoglobin (HbA1c) reference ranges can be used as diagnostic criteria for GCK-MODY discriminator [ 121 ].…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
“…Even though patients with MODY were found to differ from T1DM patients in several clinical predictors, such as C-peptide concentration [ 114 ], hsCRP [ 115 , 116 , 117 ], lipid levels, polyuria or age at diagnosis, still around 38% of the MODY patients are misdiagnosed with T1DM or T2DM [ 27 , 87 , 118 , 119 , 120 ]. In 2013 Steele et al reported that age-related glycated haemoglobin (HbA1c) reference ranges can be used as diagnostic criteria for GCK-MODY discriminator [ 121 ].…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
“…In particular, GCK-MODY is characterized by strongly cardioprotective lipid profiles of high-density lipoproteins (HDLs) subpopulations, with significantly elevated levels of large HDLs and lower levels of intermediate and small (potentially atherogenic) HDLs compared to controls [ 15 ]. Our previous work also shown GCK-MODY exhibited lower total cholesterol (TC) and low-density lipoprotein cholesterol compared to T1D [ 16 ]. A lipid-centric investigation of serum metabolic alterations accompanying perturbed glucose homeostasis in GCK-MODY, in comparison to type 2 diabetes, may thus reveal new therapeutic targets of vascular protection under concurrent hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Of which 32 cases with autoantibody-negative diabetes (male, 16 cases; female, 16 cases) were screened for ICA, GAD antibody (GADA), IA-2 and ZnT8 at diagnosis. Having at least one positive antibody and a fasting C peptide of ≥0.3 ng/ml at initial diagnosis was considered positive autoimmunity (8)(9)(10). Peripheral blood DNA was extracted from the 32 patients with autoantibody-negative diabetes and their parents for high-throughput sequencing of glucose metabolism-related genes.…”
Section: Methodsmentioning
confidence: 99%